Mortality Salience Effects on the Life Expectancy Estimates of Older Adults as a Function of Neuroticism - Molly Maxfield; Sheldon Solomon; Tom Pyszczynski; Jeff Greenberg (Journal of Aging Research)
Research has shown that reminders of mortality lead people to engage in defenses to minimize the anxiety such thoughts could arouse. In accord with this notion, younger adults reminded of mortality engage in behaviors aimed at denying vulnerability to death. However, little is known about the effects of mortality reminders on older adults. The present study examined the effect of reminders of death on older adults' subjective life expectancy. Mortality reminders did not significantly impact the life expectancy estimates of old-old adults. Reminders of death did however lead to shorter life expectancy estimates among young-old participants low in neuroticism but longer life expectancy estimates among young-old participants high in neuroticism, suggesting that this group was most defensive in response to reminders of death.